Speech - Chancellor Inauguration - by Chairperson of Amref International University Council - Kobia, Prof. Margaret (Amref International University, 2019)
On behalf of the Council, I wish to welcome all of you to this auspicious occasion of the inauguration of Amref International University’s first Chancellor. A renown Statesman and former President of Botswana, His Excellency Mr Festus Mogae.
Keywords: Inauguration; Chancellor; AMIU; Ethics; Excellence; Innovation; Commitment; Diversity; Collaboration; Excellence; inspire lasting change in Africa; Charter